2013
DOI: 10.1002/mds.25762
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in premanifest Huntington's disease

Abstract: Objective We investigated the viability of psychometrically robust executive function measures as markers for premanifest Huntington’s disease (HD). Methods Fifteen premanifest HD subjects and 42 controls were compared on the NIH EXAMINER executive function battery. This battery yields an overall Executive Composite score, plus Working Memory, Cognitive Control, and Fluency Scores that are measured on psychometrically matched scales. The scores were correlated with two disease markers, disease burden and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…Decades of research have long established that cognitive function declines in the premanifest and early stages of HD (62)(63)(64). Although several studies point to the contribution of other brain structures such as the hippocampus to learning and memory defiwith our hypothesis, KI mutant mice showed a significant increase in hippocampal RhoA activity compared with either WT, p75 +/-, or KI:p75 +/-mice ( Figure 10A).…”
Section: Discussionmentioning
confidence: 56%
“…Decades of research have long established that cognitive function declines in the premanifest and early stages of HD (62)(63)(64). Although several studies point to the contribution of other brain structures such as the hippocampus to learning and memory defiwith our hypothesis, KI mutant mice showed a significant increase in hippocampal RhoA activity compared with either WT, p75 +/-, or KI:p75 +/-mice ( Figure 10A).…”
Section: Discussionmentioning
confidence: 56%
“…HD is an auto-somal dominant inherited disorder caused by an expansion of the trinucleotide repeat cytosine-adenine-guanine (CAG). Individuals with pmHD do not yet exhibit the motor symptoms including chorea, but can exhibit cognitive or psychiatric changes (Epping et al, 2015; Paulsen et al, 2013), including working memory impairments (You et al, 2014). Caudate volume loss is present more than a decade before HD diagnosis and contributes robustly to cognitive impairment, whereas hippocampal volumes are relatively preserved and do not predict cognitive impairment (Aylward et al, 2013, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lehto (1996) demonstrated that WM tasks are correlated with the Wisconsin Card Sorting Tasks or set shifting tasks. WM abilities and executive functioning have been noted to be similarly impacted in populations such as adults with Huntington’s Disease (You et al, 2013) and children with specific language impairment (Vugs, Hendriks, Cuperus, & Verhoeven, 2014), with some authors discussing WM as a facet of executive functioning (Hofmann, Schmeichel, & Baddeley, 2012). Given the importance of WM to overall cognitive development and the execution of higher order cognitive tasks, in the NIH Toolbox, emphasis and concern was placed upon the selection of a valid and reliable task that could be utilized across the lifespan and that could be administered quickly as a core component of a 30 minute battery.…”
Section: Introductionmentioning
confidence: 99%